Herbal medicine use among urban residents in Lagos, Nigeria - Oreagba Ibrahim; Oshikoya Kazeem; Amachree Mercy (BMC, 2011)
Abstract Background Over three-quarter of the world's population is using herbal medicines with an increasing trend globally. Herbal medicines may be beneficial but are not completely harmless. This study aimed to assess the extent of use and the general knowledge of the benefits and safety of herbal medicines among urban residents in Lagos, Nigeria. Methods The study involved 388 participants recruited by cluster and random sampling techniques. Participants were interviewed with a structured open- and close-ended questionnaire. The information obtained comprises the demography and types of herbal medicines used by the respondents; indications for their use; the sources, benefits and adverse effects of the herbal medicines they used. Results A total of 12 herbal medicines (crude or refined) were used by the respondents, either alone or in combination with other herbal medicines. Herbal medicines were reportedly used by 259 (66.8%) respondents. 'Agbo jedi-jedi' (35%) was the most frequently used herbal medicine preparation, followed by 'agbo-iba' (27.5%) and Oroki herbal mixture® (9%). Family and friends had a marked influence on 78.4% of the respondents who used herbal medicine preparations. Herbal medicines were considered safe by half of the respondents despite 20.8% of those who experienced mild to moderate adverse effects. Conclusions Herbal medicine is popular among the respondents but they appear to be ignorant of its potential toxicities. It may be necessary to evaluate the safety, efficacy and quality of herbal medicines and their products through randomised clinical trial studies. Public enlightenment programme about safe use of herbal medicines may be necessary as a means of minimizing the potential adverse effects.